Heterochronic Developmental Shifts Underlying Squamate Cerebellar Diversity Unveil the Key Features of Amniote Cerebellogenesis - Macrì, Simone; Di-Poï, Nicolas (Frontiers in Cell and Developmental Biology, 2020)
Despite a remarkable conservation of architecture and function, the cerebellum of vertebrates shows extensive variation in morphology, size, and foliation pattern. These features make this brain subdivision a powerful model to investigate the evolutionary developmental mechanisms underlying neuroanatomical complexity both within and between anamniote and amniote species. Here, we fill a major evolutionary gap by characterizing the developing cerebellum in two non-avian reptile species—bearded dragon lizard and African house snake—representative of extreme cerebellar morphologies and neuronal arrangement patterns found in squamates. Our data suggest that developmental strategies regarded as exclusive hallmark of birds and mammals, including transit amplification in an external granule layer (EGL) and SHH expression by underlying Purkinje cells (PCs), contribute to squamate cerebellogenesis independently from foliation pattern. Furthermore, direct comparison of our models suggests the key importance of spatiotemporal patterning and dynamic interaction between granule cells (GCs) and PCs in defining cortical organization. Especially, the observed heterochronic shifts in early cerebellogenesis events, including upper rhombic lip (URL) progenitor activity and EGL maintenance, are strongly expected to affect the dynamics of molecular interaction between neuronal cell types in snakes. Altogether, these findings help clarifying some of the morphogenetic and molecular underpinnings of amniote cerebellar corticogenesis, but also suggest new potential molecular mechanisms underlying cerebellar complexity in squamates. Furthermore, squamate models analyzed here are revealed as key animal models to further understand mechanisms of brain organization.